2015
DOI: 10.1380/ejssnt.2015.417
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Ultra-Trace Amount of Cesium and Oxides Studied by Total-Reflection X-Ray Photoelectron Spectroscopy

Abstract: In order to clarify the chemical states of radioactive cesium sorbed in minerals such as clay, soil, sand and rock, X-ray photoelectron spectra (XPS) have been measured for cesium adsorbed on SiO2 and Al2O3 (sapphire), which are major components of these minerals. Since the number of atoms in radioactive cesium ( 134 Cs or 137 Cs) is extremely small, total reflection XPS (TR-XPS) using synchrotron radiation was applied in order to measure trace amount of cesium. For SiO2 surface, it was shown that ultra-trace … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…From Figure , it can be observed that after charging in Li electrolyte, the Cs 3d 5/2 peak almost disappears and 3d 3/2 peak is much broader. The disappearance of the 3d 5/2 peak may be due to formation of the oxide phase, i.e., SnO 2 , in which cesium atoms are adsorbed on the SnO 2 surface which lowers and shifts the intensity of the 3d 5/2 peak . The broadening of the peak may be attributed to Li ion intercalation, which may shift the Cs atom from the A site position in perovskite octahedra, resulting in a diverse chemical environment of Cs atoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From Figure , it can be observed that after charging in Li electrolyte, the Cs 3d 5/2 peak almost disappears and 3d 3/2 peak is much broader. The disappearance of the 3d 5/2 peak may be due to formation of the oxide phase, i.e., SnO 2 , in which cesium atoms are adsorbed on the SnO 2 surface which lowers and shifts the intensity of the 3d 5/2 peak . The broadening of the peak may be attributed to Li ion intercalation, which may shift the Cs atom from the A site position in perovskite octahedra, resulting in a diverse chemical environment of Cs atoms.…”
Section: Resultsmentioning
confidence: 99%
“…The disappearance of the 3d 5/2 peak may be due to formation of the oxide phase, i.e., SnO 2 , in which cesium atoms are adsorbed on the SnO 2 surface which lowers and shifts the intensity of the 3d 5/2 peak. 43 The broadening of the peak may be attributed to Li ion intercalation, which may shift the Cs atom from the A site position in perovskite octahedra, resulting in a diverse chemical environment of Cs atoms. After discharging, the 3d 5/2 peak again appears and peak shifts from 725.98 to 724.67 eV.…”
Section: Structural and Morphological Characterization Figure 1a Show...mentioning
confidence: 99%
“…So it is important to analyze the chemical states of ultra-trace amount of cesium in micaceous oxides in order to clarify the real adsorption states of radioactive cesium. In a previous paper, we have reported that XPS under total reflection (TR) shows enhanced surface sensitivity and detects trace amount of cesium adsorbed on oxides [18].…”
Section: Introductionmentioning
confidence: 99%